2021
DOI: 10.1016/j.metabol.2021.154845
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolism risk among patients with diabetes/stress hyperglycemia and COVID-19

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Stress hyperglycemia involves increases in blood glucose due to sympathetic system activation during critical illnesses such as trauma, sepsis, MI, stroke [ 11 13 ]. Calvisi et al further suggested that, even among patients with COVID-19 pneumonia, DM/stress hyperglycemia is associated higher thromboembolic risk and worse clinical outcomes [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress hyperglycemia involves increases in blood glucose due to sympathetic system activation during critical illnesses such as trauma, sepsis, MI, stroke [ 11 13 ]. Calvisi et al further suggested that, even among patients with COVID-19 pneumonia, DM/stress hyperglycemia is associated higher thromboembolic risk and worse clinical outcomes [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stress hyperglycemia involves increases in blood glucose due to sympathetic system activation during critical illnesses such as trauma, sepsis, MI, stroke [ 11 13 ]. Calvisi et al further suggested that, even among patients with COVID-19 pneumonia, DM/stress hyperglycemia is associated higher thromboembolic risk and worse clinical outcomes [ 11 ]. Stress-induced increases in the release of glucagon, cortisol and catecholamines promote the rate of glycogenolysis and gluconeogenesis, eventually leading to hyperglycemia [ 6 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes has also been shown to independently increase the risk of thrombosis in hospitalised patients with COVID-19. 22 To our knowledge, this is the first study to specifically address the significantly elevated risk of thrombosis and its associated excess mortality in males with COVID-19 relative to females. Although mortality as a function of sex was not specifically addressed in the meta-analysis of the 42 studies noted in the introduction, 5 that study also documented that thrombosis contributes to excess mortality in COVID-19.…”
Section: Discussionmentioning
confidence: 96%
“…Diabetes has also been shown to independently increase the risk of thrombosis in hospitalised patients with COVID-19. 22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation